2017
DOI: 10.1111/sltb.12358
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Association of Being Bullied and Gender with Suicide Ideations, Self‐Harm, and Suicide Attempts from Adolescence to Young Adulthood: A Cohort Study

Abstract: Longitudinal associations between being bullied during adolescence and suicide ideations, self-harm, and suicide attempts into young adulthood were examined. A large representative sample was examined in 1998 (N = 2,464, MA 13.7), 1999/2000, and 2012 to reassess the outcome measures. At all ages, bullied participants showed more suicide ideation, self-harm, and suicide attempts, regardless of gender. Bullied females showed a decrease in suicide ideation from adolescence to adulthood, while bullied males showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 55 publications
5
38
0
1
Order By: Relevance
“…We conducted sex-stratified analysis as a previous study showed that the effect of bullying on suicidality may differ by sex. 25 Using the same method, we estimated the pooled estimate for suicide attempt by type of bullying and number of days bullied in the past 30 days (0, 1-2, 3-5, 6-19, and 20-30 days). Finally, in order to assess the extent to which the association between bullying victimization and suicide attempts can be explained by loneliness, 26 we also calculated the overall pooled estimate using the same method adjusting for loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted sex-stratified analysis as a previous study showed that the effect of bullying on suicidality may differ by sex. 25 Using the same method, we estimated the pooled estimate for suicide attempt by type of bullying and number of days bullied in the past 30 days (0, 1-2, 3-5, 6-19, and 20-30 days). Finally, in order to assess the extent to which the association between bullying victimization and suicide attempts can be explained by loneliness, 26 we also calculated the overall pooled estimate using the same method adjusting for loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study failed to ascertain the associations between different types of bullying victimization and suicidal behaviours. A longitudinal study of 2464 Norwegian adolescents aged 12–15 years observed that exposure to bullying during adolescence increased the risk of both suicidal ideation and attempt among boys and girls, and this effect persisted into young adulthood [52]. Another cohort study of 5302 Finnish children showed that the association between being bullied at age 8 years and later suicidal attempts varied by sex.…”
Section: Discussionmentioning
confidence: 99%
“…(3) SA: "I try to commit suicide." Participants were considered to have self-harm, SI, or SA (coded 1) if the response was 2 = "sometimes, " 3 = "often, " or 4 = "almost, " while they were coded 0 if the response was 1 = "never" (40).…”
Section: Self-harm Suicidal Ideation and Suicide Attemptsmentioning
confidence: 99%